Comparative Evaluation of Some Commercial Clopidogrel Tablets Available in Yemen - Bassam Abduh Ali; Mohammed Gameel Al-haddad; Abdullah Ahmed Areqi (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Clopidogrel is a medication to reduce the risk of heart disease and taken orally. Quality of drug characterizes the production process and every phamaceutical company strives for it but often it is very difficult to achieve. This study was to investigate quality control parameters of some marketed Clopidogrel tablets. To assess the quality, eight different marketed brands of Clopidogrel 75 mg tablets available in Yemeni market collected from different pharmacies in Hodeida city. Different quality parameters like weight variation, hardness, thickness and friability were determined according to established protocols. Then the in-vitro dissolution test, potency, disintegration time were also carried out. UV-spectrophotometer was used to determine the percentage released and assay at 218 nm. All the brands comply the requirements of Pharmacopoeia as they showed acceptable weight variation range. Friability of all brands was less than 1% and no significant differences in disintegration times as they disintegrated within 15 minutes. In case of dissolution profile, all brands except C6 showed acceptable dissolution time as they released more than 60% of drug in 45 minute. The hardness of only two brands was within the range. All brands also meet the potency specifications. This study suggested that most commercially Clopidogrel tablets in Yemen maintain the quality and comply with the pharmacopeia specifications.